Individual Variation in Thermal Reaction Norms Reveals Metabolic-Behavioral Relationships in an Ectotherm - Baškiera, Senka; Gvoždík, Lumír (Frontiers in Ecology and Evolution, 2022)
Ectothermic organisms respond to rapid environmental change through a combination of behavioral and physiological adjustments. As behavioral and physiological traits are often functionally linked, an effective ectotherm response to environmental perturbation will depend on the direction and magnitude of their association. The role of various modifiers in behavioral-physiological relationships remains largely unexplored. We applied a repeated-measures approach to examine the influence of body temperature and individual variation on the link between resting metabolic rate (RMR) and exploratory locomotor activity (ELA) in juvenile Alpine newts, Ichthyosaura alpestris. We analyzed trait relationships at two body temperatures separately and as parameters, intercepts and slopes, of thermal reaction norms for both traits. Body temperature affected the level of detectable among-individual variation in two different directions. Among-individual variation in ELA was detected at 12°C, while RMR was repeatable at 22°C. We found no support for a link between RMR and ELA at either temperature. While analysis of intercepts revealed among-individual variation in both traits, among-individual variation in slopes was detected in RMR only. Intercepts were positively associated at the individual, but not the whole-phenotypic, level. For ELA, the target of selection should be individual trait values across temperatures, rather than their thermal sensitivities. The positive association between intercepts of thermal reaction norms for ELA and RMR suggests that phenotypic selection acts on both traits in a correlated fashion. Measurements at one body temperature and within-individual variation hide the metabolic-behavioral relations. We conclude that correlative studies on flexible behavioral and physiological traits in ectotherms require repeated measurement at two or more body temperatures in order to avoid misleading results. This approach is needed to fully understand ectotherm responses to environmental change and its impact on their population dynamics.